A review on the visible light active modified photocatalysts for water splitting for hydrogen production. (15th December 2021) - Chen, Wei‐Hsin; Lee, Jung Eun; Jang, Seong‐Ho; Lam, Su‐Shiung; Rhee, Gwang Hoon; Jeon, Ki‐Joon; Hussain, Murid; Park, Young‐Kwon
Summary: There are various methods to produce hydrogen from water splitting as a substitute energy resource for fossil fuels in accordance with the global environmental crisis. Among these, water photocatalysis is considered one of the most renewable and sustainable processes simulated the solar energy utilized system in nature. During a half century, different kinds of photocatalysts were developed to convert photon energy into chemical energy to induce redox potential under visible light irradiation condition. In the beginning step, semiconductor materials, such as transition metal oxides, were explored extensively to use as a photocatalyst for hydrogen generation. However, semiconductor has limitations to act as an effective photocatalyst for water splitting due to the large band gap and recombination of charge carriers. Therefore, several kinds of modifications of structure or components have been studied to design visible light active photocatalysts for water splitting to generate hydrogen. Their performance was improved substantially by adding a noble metal or sensitizer to adjust the band gap and reduce the recombination of photoinduced charge carriers. Considering solar light‐induced photocatalytic hydrogen generation, various visible light active photocatalysts have been derived from carbon chain organic compounds and lattice crystals. This review classifies the visible light active photocatalysts as follows: (a) structural and chemical components of modified graphitic carbon nitride (g‐C3 N4 ), (b) exfoliated perovskites, and (c) π‐bond conjugated polymers to produce hydrogen from water splitting. The hydrogen evolution efficiency of photocatalysts shows a great difference under visible light ( λ > 400 nm) irradiation according to the three‐dimensional structure and electron transfer pathway. This is because the capability of restricting the recombination of photoinduced charge carriers and the band gap between the valence band and the conduction band of photocatalysts is dependent on the morphology and electrostatic interactions among components. This paper reviews visible light photocatalysts, that is, g‐C3 N4 based materials, layered perovskites, and conjugated polymers, to provide integrated insight into photocatalytic water splitting to obtain hydrogen. Abstract : A variety of methods to produce hydrogen energy from water splitting as a substitute energy resource of fossil fuels have been reported. Among these, water photocatalysis is regarded as one of the most renewable and sustainable processes. In this work, based on recently published literature, visible light photocatalysts that is, g‐C3 N4 based materials, layered perovskites, and conjugated polymers are reviewed to provide integrated insight regarding photocatalytic water splitting to obtain hydrogen.